Compliance to prenatal Iron and Folic acid supplement and associated factors among women during pregnancy in South East Ethiopia: A Cross-sectional study (Global Journal of Medical Research, 2017)
Background: Nutritional anemia is one of the leading causes of morbidity and mortality among pregnant women in developing country. Several studies have shown that prenatal iron and folic acid supplement for three months and more during pregnancy plays a great role in preventing maternal morbidity and mortality. The aim of this study was to assess compliance of prenatal iron and folic acid supplement and its associated factors during Antenatal Care in Goba District South East Ethiopia. Methods: A community based cross-sectional study was conducted from March to May, 2014 in Goba District. A total of 405 mothers who give birth in the last six months were selected using systematic random sampling technique. Data were collected using pretested questionnaire by interview and then entered and analyzed using SPSS version 20. Both Bivariate and multivariate logistic regression were carried out to see significant association. Variables with P-value less than 0.05 were considered as significant in the multivariate analysis. Results: The compliances rate to IFA supplement was found out to be 18%. Educational status of mother (AOR=0.24 (95% CI 0.63-0.97)), knowledge on anaemia (AOR =0.41 (95% CI 0.20-0.84)), knowledge on benefit of iron folic acid (AOR =0.38 (95% CI 0.20-0.77), receiving health education on Iron Folic acid supplement during prenatal visit ) were found to be factors associated with compliances to iron folic acid supplement.
Keywords: iron; folic acid; compliances to IFA; women; southeast Ethiopia